2021
DOI: 10.1111/vde.13010
|View full text |Cite
|
Sign up to set email alerts
|

Survey of cytokines on ocular surfaces of atopic dogs by multiplex analysis using two sampling methods – a pilot study

Abstract: Background -Conjunctivitis in atopic dogs has already been described yet is rarely observed, and likely underdiagnosed in practice.Objectives -To assay various cytokines in tears and conjunctivae from atopic and normal dogs, and to compare canine atopic dermatitis-associated conjunctivitis with controls.Animals -Ten atopic and ten normal client-owned dogs.Methods and materials -Ocular surfaces were sampled bilaterally in a prospective study, using two different methods. Tear samples were obtained with a steril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In a recent pilot study, concentrations of cytokines were measured by a Luminex assay in the tears and the conjunctiva of atopic dogs and compared with the concentrations detected in normal dogs. IL-8 was found to be over-expressed in conjunctiva and tears of atopic dogs despite subtle conjunctival symptoms [ 30 ]. Finally, a recent study showed that the plasma concentrations of IL-8, IL-7, and IL-15 cytokines were elevated in canine AD patients compared to in control dogs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent pilot study, concentrations of cytokines were measured by a Luminex assay in the tears and the conjunctiva of atopic dogs and compared with the concentrations detected in normal dogs. IL-8 was found to be over-expressed in conjunctiva and tears of atopic dogs despite subtle conjunctival symptoms [ 30 ]. Finally, a recent study showed that the plasma concentrations of IL-8, IL-7, and IL-15 cytokines were elevated in canine AD patients compared to in control dogs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, significantly increased IL-8/CXCL8 concentrations have been reported in previous studies that analyzed cytokines by swabbing the cerumen or occlusal surface of dogs with atopic dermatitis (6, 7). In an analysis of cytokine expression in conjunctival swabs, IL-8 was the only cytokine that was significantly increased in atopic dogs, showing a positive correlation with conjunctival and pruritus scores (7). In addition, the concentration of IL-8 is also significantly higher in the ears of atopic dogs than in healthy dogs (6).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, research on non-invasive methods for analyzing skin cytokine expression has recently become of interest. These methods employ collecting samples from the cerumen, ocular surface, and stratum corneum by tape stripping (3,(5)(6)(7). These non-invasive methods allow sampling from many patients and analysis of the expression of cytokines in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 is a potent chemoattractant for neutrophils and a proinflammatory mediator. It has been shown to be significantly elevated in some atopic dogs [1], including ear canals [28] and conjunctivae [29], but also in ear canals infested with O. cynotis [28]. Its 45% reduction compared to baseline is likely linked to the decrease in aural inflammation.…”
Section: Discussionmentioning
confidence: 99%